How the root bacterial community of Ficus tikoua responds to nematode infection: enrichments of nitrogen-fixing and nematode-antagonistic bacteria in the parasitized organs - Meng, Xiang-Rui; Gan, Yu; Liao, Li-Jun; Li, Chao-Nan; Wang, Rong; Liu, Mei; Deng, Jun-Yin; Chen, Yan (Frontiers in Plant Science, 2024)
Plant-parasitic nematodes (PPNs) are among the most damaging pathogens to host plants. Plants can modulate their associated bacteria to cope with nematode infections. The tritrophic plant–nematode–microbe interactions are highly taxa-dependent, resulting in the effectiveness of nematode agents being variable among different host plants. Ficus tikoua is a versatile plant with high application potential for fruits or medicines. In recent years, a few farmers have attempted to cultivate this species in Sichuan, China, where parasitic nematodes are present. We used 16S rRNA genes to explore the effects of nematode parasitism on root-associated bacteria in this species. Our results revealed that nematode infection had effects on both endophytic bacterial communities and rhizosphere communities in F. tikoua roots, but on different levels. The species richness increased in the rhizosphere bacterial communities of infected individuals, but the community composition remained similar as compared with that of healthy individuals. Nematode infection induces a deterministic assembly process in the endophytic bacterial communities of parasitized organs. Significant taxonomic and functional changes were observed in the endophytic communities of root knots. These changes were characterized by the enrichment of nitrogen-fixing bacteria, including Bradyrhizobium, Allorhizobium–Neorhizobium–Pararhizobium–Rhizobium, and nematode-antagonistic bacteria, such as Pseudonocardia, Pseudomonas, Steroidobacter, Rhizobacter, and Ferrovibrio. Our results would help the understanding of the tritrophic plant–nematode–bacterium interactions in host plants other than dominant crops and vegetables and would provide essential information for successful nematode management when F. tikoua were cultivated on large scales.